The ICA: a force for the public good. Issue 1 (1st December 2022) - Fricker, David
Abstract : For anyone working within the field of archives or records management, the ICA has a special value. As the peak international organization for archives, the ICA offers its collective membership a powerful platform upon which to influence legislatures, governments and policy-makers. Within the professional community, it offers our members a pathway that elevates each of us from a skilled practitioner to a true professional. The significance of this should not be underestimated. A skilled practitioner would aspire to be highly competent and technically literate in the field of archives, however, a professional aspires for much more, taking on a commitment to a code of ethics, the development of a professional community, and the virtuous pursuit of public good through the work we do. By drawing on just a few examples from a long list of its achievements, this article demonstrates the reach and influence of the ICA affecting the issues that genuinely matter to most to people in the world, such as inequality, access to justice, freedom of speech, open government, climate change and decolonization.